THE EFFECT OF NUMBER OF MEETINGS OF THE BOARD OF COMMISSIONERS, INDEPENDENT COMMISSIONERS, AUDIT COMMITTEE AND OWNERSHIP STRUCTURE UPON THE EXTENT OF CSR DISCLOSURE - Raphita Fauzyyah; Sistya Rachmawati (The Accounting Journal of Binaniaga, 2018)
This study aims to investigate the characteristics of corporate governance that affect the level of Corporate Social Reponsibility (CSR) disclosure in the firms that have business operations in the manufacturing field in Indonesia. Characteristics of the corporate governance used in this study are the number of meetings conducted by the board directors, independent commissioners, audit committee, managerial along with foreign that have ownership, and ownership concentration. The level of work on CSR disclosure was measured by using company’s social disclosure index (or later will be referred to as CSDI) based on standard used, namely Global Reporting Initiative (or later to be discussed as GRI) which will report standard items and then disclose the items in the firm’s annual report. This study also used the levels of the firm’s board commissioners, the composition or arrangement of women in the board, public along with institution ownership, and the control variables of this study was environment performance. The populations used in this study were firms that run business in the manufacture fieldwork sector that registered in Indonesian Stock Exchange (or known as IDX) in the 2014-2017. This disquisition using the method sampling purposive, the total population was reduced to 88 annual reports of firms that run mining business to be sampled in this research. The technique of data analysis used multiple regression method to determine whether there are relationship owned by the characteristics of corporate governance with CSR disclosure. The conclusion of the disquistion showed that composition of managerial ownership does not have significant and positive influence on the extent or level of CSR. The outcomes of the investigations also show that the two control variables have a significant influence on the extent or level of CSR.Key words:  audit committee, corporate social responsibility, ownership structure, board characteristics, composition of women on board, and environment performance